Efektivitas Psikoedukasi Melalui Musik terhadap Peningkatan Self Esteem Remaja Beresiko - Sasmita, Heppi; Tasman; Deviaroza; Rachmadanur, N; Muchtar, Murniati (Jurnal Kesehatan Komunitas, 2024)
The development of adolescence is very important throughout the life cycle. At this time, there is a change in adolescents' experience of fundamental physical and psychological. They also do not yet have effective coping experiences, causing difficulties in managing their emotions and behavior. The low self-esteem in adolescents causes them to be unable to maximize their potential. This study aimed to see an increase in self-esteem in at-risk adolescents by applying psychoeducation through music at SMPN 39 Padang. This quantitative study was designed in a "Quasi-experimental pre-posttest control group" by applying psychoeducational therapy through music using social media. The results of the analysis showed that there was an effect of psychoeducation through music on changes in the self-esteem of at-risk adolescents before and after the intervention in the treated group. The results of the statistical test can be concluded that there was a significant increase in self-esteem before and after giving psychoeducational therapy through music (Pvalue <0.05). The average self-esteem of at-risk adolescents in the group that received psychoeducation through music was 1.85 lower than the group that did not receive psychoeducation through music. Self-esteem in adolescents at risk differed significantly between the group that received psychoeducation through music and the group that did not receive psychoeducation through music.